On the asymptotic analysis of the high-order statistics of the channel capacity over generalized fading channels - Yilmaz, Ferkan (Tubitak Scientific & Technological Research Council Turkey, 2020)
In this article, we provide further asymptotic analysis to the higher-order statistics (HOS) of the channel capacity over generalized fading channels, especially by proposing simple and closed-form expressions each of which can be easily computed as a tight bound revealing the existence of constant gap between the actual and asymptotic HOS of the channel capacity in the limit of both high and low signal-to-noise ratios. As such, we show that these closed-form asymptotic expressions are insightful enough to comprehend the diversity gains. The mathematical formalism we followed in this article is illustrated with some selected numerical examples that validate the correctness of our newly derived asymptotic results.
Keywords: Higher-order ergodic capacity; higher-order amount of fading; generalized fading channels; DIVERSITY; Computer Science; Engineering